Staging Orality: Speaking as Performancein School life (2017)
The objective of this article is to present a revision of the Basic Learning Rights (BLR) and the Basic Standards for Language Competences (BSLC), focusing on the conception of orality proposed in them, specifically for grades sixth to eleventh. The article also makes a comparison between the ideas of some of the most relevant authors in the field of orality the field of orality, whose work has national and international recognition; placing a special focus on the authors who have created bounds between the concepts of orality and performance. As a product of this analysis, new pedagogical strategies will be proposed, based on experiences gathered with the students from the study group El discurso oral en el Quindío: de la Academia a la cotidianidad (DOQAC) [Oral speech in Quindío: from Academia to Everyday life], in order to explore and experiment some of the characteristics of orality that are barely suggested in the BLR and BSCL